Hypercoagulability in patients with haematological neoplasia: No apparent initiation by tissue factor - Negaard, Helene F. S.; Iversen, Per Ole; Østenstad, Bjørn; Iversen, Nina; Holme, Pål A.; Sandset, Per Morten (Thrombosis and Haemostasis, 2008)
Patients with haematological malignancies carry increased risk of venous thrombosis (VT). However, the mechanisms that link these malignancies to activated coagulation have not been fully identified. Since anti-haemostatic agents are studied in clinical trials for their potential to prolong survival in cancer patients, a detailed characterisation of haemostatic markers in cancer subtypes is needed. Hence, in this study, we measured the plasma concentrations and mRNA expression in blood mononuclear cells of haemostatic parameters in 93 patients with haematological neoplasias (acute myeloid leukaemia, chronic lymphatic leukaemia, multiple myeloma, and non-Hodgkin’s lymphoma) before start and after completion of cancer therapy. At diagnosis we found activation of coagulation and fibrinolysis, especially in patients with acute myeloid leukaemia. This hypercoagulation was not associated with increased levels of tissue factor (TF) or factor VII (fVII) antigen or mRNA, or levels of activated fVII. In conclusion we found a hypercoagulable state in patients with haematological malignancy that did not seem to be initiated by TF.
Keywords: Coagulation; leukaemia; lymphoma; myeloma; tissue factor